Mechanochemical synthesis of N-salicylideneaniline: thermosalient effect of polymorphic crystals - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nangia, Ashwini (IUCRJ, 2017)
Polymorphs of the dichloro derivative of N-salicylideneaniline exhibit mechanical responses such as jumping (Forms I and III) and exploding (Form II) in its three polymorphs. The molecules are connected via the amide N-H center dot center dot center dot O dimer synthon and C-Cl center dot center dot center dot O halogen bond in the three crystal structures. A fourth high-temperature Form IV was confirmed by variable-temperature single-crystal X-ray diffraction at 180 degrees C. The behaviour of jumping exhibited by the polymorphic crystals of Forms I and III is due to the layered sheet morphology and the transmission of thermal stress in a single direction, compared with the corrugated sheet structure of Form II such that heat dissipation is more isotropic causing blasting. The role of weak C-Cl center dot center dot center dot O interactions in the thermal response of molecular crystals is discussed.
Keywords: crystal design; crystal engineering; Halogen bonding; hydrogen bonding; intermolecular interactions; materials science; mechanochemistry; polymorphism

Polyoxometalate clusters: inorganic ligands for functional materials - Dey, Chandan (Journal of Cluster Science, 2022)
Research in polyoxometalates (POMs) is a diverse growing field with variations in application. POMs are consisting of metal ion and oxide. Peripheral oxides of POM can share spare electron pairs to behave as ligands. This property of POM was utilized for constructing coordination polymers (CPs), synthesizing transitional metal substituted POM for catalysis, synthesizing and stabilizing nano-particles, etc. POM connected structures have provided an opportunity of heterogenization of some homogeneous POM catalyst. Furthermore, diamagnetic POM ligands have been suitable for stabilizing and isolating magnetic ions inside clusters. The scope of this review is to summarize the role of POMs as ligands to prepare POM based CPs, synthesize and stabilize metal nano-particles and isolate magnetic ion or unit.
Keywords: Coordination polymer; Inorganic ligand; materials science; polyoxometalates; synthesis design